2020
DOI: 10.3389/fonc.2020.593461
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Side Effects of EGFR-Inhibitor ABT-414 in Recurrent Glioblastoma: A Long-Term Safety Study

Abstract: This study aimed to prospectively evaluate, on a long-term basis, corneal side effects secondary to compassionate administration of epidermal growth factor receptor (EGFR) inhibitor depatuxizumab mafodotin (ABT-414) in patients affected by EGFR-amplified recurrent glioblastoma. Fifteen patients with a median follow-up of 4.3 months after treatment discontinuation were enrolled. Each patient underwent full ophthalmologic examination including in vivo corneal confocal microscopy (CCM). No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Remarkably, other off-label drugs previously adopted for the treatment of MM were shown to induce corneal epithelial alterations, probably resulting from drug accumulation in the epithelium and subsequent cellular apoptosis. Among these, depatuximab mafoditin, which acts as an epidermal growth factor receptor inhibitor, caused a reversible corneal epitheliopathy in treated patients, characterized by multiple and diffuse hyper-reflective spots, progressive sub-basal nerve plexus fragmentation and by the appearance of cystic structures at the level of corneal epithelium [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, other off-label drugs previously adopted for the treatment of MM were shown to induce corneal epithelial alterations, probably resulting from drug accumulation in the epithelium and subsequent cellular apoptosis. Among these, depatuximab mafoditin, which acts as an epidermal growth factor receptor inhibitor, caused a reversible corneal epitheliopathy in treated patients, characterized by multiple and diffuse hyper-reflective spots, progressive sub-basal nerve plexus fragmentation and by the appearance of cystic structures at the level of corneal epithelium [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased expertise regarding the management of Depatux-M has been gained by neuro-oncologists which have previously participated in the INTELLANCE 1 and 2 trials; another key factor contributing the management of ocular toxicity is that all patients enrolled in our study were followed by a dedicated ophthalmologist. Indeed, it was already demonstrated that the ocular side effects caused by Depatux-M can be reversible and moderate if carefully managed [ 19 , 20 ]. In our study, Depatux-M dose reduction occurred in 17% of patients versus 12% reported in the previous phase 1 study, while dose delays occurred in only 28% versus the 58% seen in the prior study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the following are of interest: i) Molecularly targeted therapy; ii) anti-angiogenic drugs; iii) GSC targeting; iv) microRNAs; v) immunotherapy; vi) nanotherapy; vii) gene therapy; and viii) oncolytic viruses (59). As of 2021, a number of compounds have successfully gone through all phases of drug development and have been approved for clinical testing on human subjects (21,37,38,42,44,54,60,61,(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). They are summarized in Table II.…”
Section: Pharmaceutical Products Tested In Clinical Trialsmentioning
confidence: 99%
“…In the era of precision medicine, a combination of molecular techniques can also be applied to target the unique tumour characteristics of individual patients (18)(19)(20). To improve the outcome, a comprehensive list of parameters must be understood, including the GBM microenvironment, the pharmacokinetic and pharmacodynamic profiles of the drug of interest, in addition to the delivery and safety profiles (21). Although some drugs (TMZ, lomustine, carmustine and bevacizumab) have obtained Food and Drug Administration (FDA) approval for GBM treatment, others are currently at different stages of clinical trial testing (22).…”
Section: Introductionmentioning
confidence: 99%